The Quest for Education: Racism, Paradox, and Interest Convergence in the Life of George Washington Carver - Ron Wilson; Kay Ann Taylor (Educational Considerations, 2020)
George Washington Carver is known primarily for his life and work at Tuskegee Institute in Alabama. This historical research provides insight prior to that time and into his journey from Missouri to several towns in Kansas, and then to Iowa. The intersection of race, education, and philanthropy combined to guide the culmination of his life’s work—in concert with interest convergence.
Keywords: George Washington Carver; biography; interest convergence; intersectionality